2014
DOI: 10.2319/010814-28.1
|View full text |Cite
|
Sign up to set email alerts
|

Force decay evaluation of thermoplastic and thermoset elastomeric chains:A mechanical design comparison

Abstract: TS chains decayed less than TP chains, and chain loop retraction was beneficial only when using OrTP chains. Contrary to the interchangeable use of TP and TS chains in the published literature and in clinical practice, this study demonstrates that they perform differently under stress and that a clear distinction should be made between the two.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 11 publications
0
23
0
8
Order By: Relevance
“…Some companies make elastomeric chains in both TP and TS materials, and a recent study by Masoud et al 6 compared the two in vitro. They showed that TS elastomeric chains decayed less than did TP elastomeric chains.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some companies make elastomeric chains in both TP and TS materials, and a recent study by Masoud et al 6 compared the two in vitro. They showed that TS elastomeric chains decayed less than did TP elastomeric chains.…”
Section: Introductionmentioning
confidence: 99%
“…The second type is synthetic elastomers, which are used in elastomeric chains, elastomeric ligatures, and elastic threads and are usually referred to as "alastiks." 1,3,6 Synthetic elastomers are made mainly from polyurethanes 8,12 and can either be thermoplastic (TP) or thermoset (TS). 6 TP materials can be made plastic and are moldable at high temperatures, while TS materials are irreversibly cured during the process of manufacturing, are not remoldable, and will burn at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations